(untitled) (INNOVATIVE ECONOMY, 2024)
Honcharenko O.V., Chornovol O.Yu. CONCEPTUAL PRINCIPLES OF INSTITUTIONAL DESIGN OF ECONOMIC DYNAMICS IN THE CONTEXT OF STABILIZATION OF THE NATIONAL ECONOMY Purpose. The aim of the article is to generalize the conceptual principles of institutional design and determine the elements of institutional support for the development of innovations in the national economy. Methodology of research. The theoretical and methodological basis of the research is the structural and functional analysis to determine the direct and indirect institutional elements of the regulation of economic dynamics; a systematic approach to the generalization of the conceptual foundations of institutional design of institutes of innovative direction; institutional analysis of the advantages and costs of institutional design of innovative institutions. Findings. It is emphasized that the implemented norms and institutions of innovative direction in the national economy are not able to produce positive effects due to the overwhelming imperfection of the institutional environment, which nullifies the introduction of incentives. Institutions and institutions that focus on the implementation of economic development are opposed by formal norms that hinder progress. It was established that institutional design is implemented through the adjustment of existing formal norms; introduction of new institutional norms, introduction of additional or new institutions or institutes; transplantation of economic institutions. It is argued that the transplantation of economic institutions from a more developed model is carried out with the help of "shock" therapy, "cultivation", introduction of the format of progressive changes through the creation of "intermediate institutions". Originality. It is substantiated that the technology of "growing" an economic institution is more attractive for the initial conditions that are characteristic of the national economy, because the time for adaptation of transplanted formats is shortened and the risks of dysfunctions are minimized, and the prospect of "rejection" of institutional elements due to relatively small design changes is limited. The only problem is the possibility of rapid "routinization" of intermediate forms of economic institutes, which will not contribute to the prompt implementation of the "desired" format of the institute and slows down economic dynamics. It is emphasized that the formation of intermediate institutes of innovation development in the economy must be implemented through successive forms of the institute of innovation within the stages of the implementation of the model of the innovation process. Thus, at the stages of providing financing for innovative activities, state financing can be supplemented by the introduction of such intermediate formats as state credit and state partnership; the stage of production of innovations – diversification and unification of various scientific structures into technoparks and clusters; the stage of innovation development can be strengthened by attracting state support for the innovation process (investment, infrastructure, communication, fiscal); for the stage of diffusion, the creation of scientific and innovative centres and the formation of innovative infrastructure are considered important. Practical value. The theoretical and methodological provisions of the study generalize and deepen the practical principles of institutional design of innovative development of the national economy. Key words: efficiency, innovation, innovative development, national economy, institutional dysfunction, institutional design, institute, stabilization of the national economy.